National extension policy and state-level implementation: The case of Cross River State, Nigeria - Ogunniyi, Adebayo; Babu, Suresh Chandra; Balana, Bedru; Andam, Kwaw S. (International Food Policy Research Institute, 2020)
Agricultural extension plays a number of important roles in the growth and transformation of the agricultural sector, including improving agricultural productivity and food security and reducing hunger and malnutrition. Extension programs and interventions that will achieve significant impacts in terms of behavior and practice changes, as well as agricultural productivity increase, will succeed as a result of suitable policy formulation and an effective implementation process. Ultimately, agricultural extension reform requires policy vision and determination and a state-level strategy that can be implemented. This paper documents issues, challenges, constraints, and potential solutions and opportunities in implementing the national extension policy (NEP) at the state level in Nigeria, using Cross River State as a case study. We use both quantitative and qualitative methods, in the form of descriptive statistical analysis and an inclusive consultative process with a focus on the multistakeholder participatory model, respectively. The descriptive results show that, generally, there is low access to agricultural extension service across commodities and their respective values chains in Cross River State. We also document interesting insights from the multistakeholder consultative process. We find that collaboration and partnership between private and public extension service providers is key to developing a sustainable extension, advisory, and support service in Cross River State. We also found that coordination and standardization of the activities of the extension service providers is a way to avoid pollution of the agricultural innovation system in the state. Funding of extension services is another important factor affecting the effective implementation of the NEP. We therefore suggest that agricultural extension services can be funded through decentralization, involvement of farmers’ associations and nongovernmental organizations, contracting out of extension services, public-private partnerships, privatization, and embedding advisory services in other types of contracts. The results of this study further validate our approach of using multistakeholder engagement at the state level as an effective and insightful method of implementing the NEP at the state level.